2015
DOI: 10.1016/j.fshw.2015.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Phenolics from grapefruit peels inhibit HMG-CoA reductase and angiotensin-I converting enzyme and show antioxidative properties in endothelial EA.Hy 926 cells

Abstract: This study sought to investigate the possible mechanisms for the use of phenolic extracts from grapefruit peels in the management/ prevention of cardiovascular complications.The effects of the phenolic extracts on key enzymes relevant to cardiovascular diseases [3-hydroxy-methyl-3-glutaryl coenzyme A reductase (HMG-CoA reductase) and angiotensin-I converting enzyme (ACE)], cellular antioxidant activity in human endothelial cells (EA.Hy 926) and radicals [1,1-diphenyl-2 picrylhydrazyl (DPPH) and 2,2'-Azino-bis(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 30 publications
(29 reference statements)
3
40
0
Order By: Relevance
“…These results are potentially important because they imply that toranja peels are a greater source of antioxidants than the interior section (juice), which is in agreement with other studies (Ademosun et al, ; Toh et al, ). And also indicated is that the compounds involved in defense reactions of the citrus fruit are found in greater amounts in the superficial layer; therefore, the antioxidant activity should be related to the part in the fruit where protection against lipid oxidation is needed.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…These results are potentially important because they imply that toranja peels are a greater source of antioxidants than the interior section (juice), which is in agreement with other studies (Ademosun et al, ; Toh et al, ). And also indicated is that the compounds involved in defense reactions of the citrus fruit are found in greater amounts in the superficial layer; therefore, the antioxidant activity should be related to the part in the fruit where protection against lipid oxidation is needed.…”
Section: Resultssupporting
confidence: 91%
“…Quercetin was used as a reference in the assays because it represents one of the major phenolic compounds found in citrus peels (Ademosun et al, ), and it has been reported that it can modulate Phase II metabolism inducing QR (Chen & Blumberg, ). Quercetin inhibited DPPH by 69.7 ± 2.59% at the minimum concentration tested (0.001 mM).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations